FIGURALCREATIVITY IN STUDENTS MAJORING IN ARCGITECTURAL ENGINEERING - Ala, Jenifer Ruth Lapa; Marianah Dinah Charlota Lerik,; R. Pasifikus Christa Wijaya, (Journal of Innovation Research and Knowledge, 2025)
This study aims to determine the level of figural creativity among students of the Architectural Engineering Department at Nusa Cendana University, focusing on the ability to generate new ideas through drawings, as assessed using the Torrance Tests of Creative Thinking (TTCT). The research employs a quantitative descriptive method involving 66 students as samples. Data were collected through a figural test that evaluated the aspects of fluency, flexibility, originality, and elaboration. The results show that the majority of students fall into the average creativity category (55%). This study indicates that most students of the Architectural Engineering Department at Nusa Cendana University possess a moderate to high level of figural creativity. The environmental factors within the Architecture Department at Undana provide a conducive setting for the development of figural creativity, illustrating that Architecture Engineering students have a strong capacity for figural creativity